2017
DOI: 10.1111/bld.12192
|View full text |Cite
|
Sign up to set email alerts
|

Internet use, risks and online behaviour: The view of internet users with intellectual disabilities and their caregivers

Abstract: Accessible Summary• Going online is important because we can learn, meet people, and get info. But some actions by others or by ourselves can be harmful.• We wanted to find out how people with intellectual disabilities in Spain go online and the problems they have using it.• We asked 77 adults with intellectual disabilities and 68 caregivers to answer questions about how people with intellectual disabilities use the Web.• We found that people with intellectual disabilities prefer smartphones to go online, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
92
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 20 publications
(61 reference statements)
16
92
0
6
Order By: Relevance
“…On one side, specific benefits have been identified for people with ID in their use of the Internet such as social interaction, access to support groups (Molin, Sorbring, and Löfgren-Martenson 2015), self-determination, learning and entertainment (Chadwick et al 2013). The studies show that the device most used by them to access the Internet is the smartphone (Didden et al 2009;Gutiérrez and Martorell 2011) and that the activities they usually do online are watching videos, chatting with friends, or reading and writing on social networks (Chiner, Gómez, and Cardona 2017a).…”
Section: Benefits and Risks Of Internet Use For People With Idmentioning
confidence: 99%
“…On one side, specific benefits have been identified for people with ID in their use of the Internet such as social interaction, access to support groups (Molin, Sorbring, and Löfgren-Martenson 2015), self-determination, learning and entertainment (Chadwick et al 2013). The studies show that the device most used by them to access the Internet is the smartphone (Didden et al 2009;Gutiérrez and Martorell 2011) and that the activities they usually do online are watching videos, chatting with friends, or reading and writing on social networks (Chiner, Gómez, and Cardona 2017a).…”
Section: Benefits and Risks Of Internet Use For People With Idmentioning
confidence: 99%
“…Access to internet-enabled devices has historically shown higher access to computers than mobile phones among people with intellectual disabilities: 50% have access to a computer and about 20% to a mobile phone (Palmer et al, 2012). However, the digital development is rapid and a recent study of adults with intellectual disabilities showed a higher possession of smartphones, 90%, than computers, 61% (Chiner et al, 2017). The internet is used among people with intellectual disabilities for entertainment (Ramsten et al, 2018) and social contact, but challenges are reported with linguistic skills and handling personal settings for social media use (Shpigelman and Gill, 2014;Shpigelman, 2018).…”
mentioning
confidence: 99%
“…Comparative studies of internet use between people with intellectual disabilities and the general population are required to investigate digital participation and equalities and inequalities, e.g. regarding risks with the internet (Alper and Goggin, 2017;Chiner et al, 2017). To the authors' knowledge, there is only one comparative empirical study focusing on internet use of persons with and without intellectual disabilities (Jenaro et al, 2017).…”
mentioning
confidence: 99%
“…The devices most used for AR intervention are mobile devices, especially smartphones, due to their price, accessibility and social inclusion in their use. This fact is relevant since several studies have shown that the device most commonly used by people with ID is the smartphone (Didden et al, 2009;Chiner, Gómez & Cardona, 2017;Gutiérrez & Martorell, 2011).…”
Section: Discussionmentioning
confidence: 99%